Enhancing Hydrogen Storage in AZ31 Alloy through Pd/G Composite - Huang, Song-Jeng; Lai, Chen-Ju; Rajagopal, Veeramanikandan; Chang, Wen-Lie (Journal of Research Updates in Polymer Science, 2023)
In this research, we investigated the catalytic effects of Palladium/Graphene(Pd/G) on AZ31 alloy for hydrogen storage. X-ray diffraction (XRD) analysis, scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (SEM-EDS) were employed to confirm the homogeneous distribution of AZ31 and observe phase changes after mechanical alloying with the catalysts. The hydrogen storage properties of AZ31 with catalysts were systematically examined, and the time of maximum reaction rate for nucleation was determined using Avarami Plot. The results of the study show that the incorporation of 2% Pd/G resulted in the fastest hydrogen absorption and desorption time, taking 200 seconds to achieve 90% hydrogen storage with a maximum of 6.04 wt%. The corresponding maximum hydrogen desorption occurred in 694 seconds, reaching 6.03 wt%. Consequently, the introduction of 2% Pd/G catalyst proved to be effective in significantly enhancing the hydrogen ab/desorption rates of AZ31 alloy.